Electrical Maintenance Training for Three-Wheeled Motor Vehicles - Hermawan, Fendi; Setiawan, Andre; rimet, junet; Rahman, Iqbal Fathur Rahman; Riyono, Yoga Pratama; Baidlowi, Achmad Irsyad; Ridlo, Muhammad Zainur Ridlo (Universitas Muhammadiyah Jember, 2025)
This electrical maintenance training on three-wheeled motor vehicles aims to improve participants’ understanding and skills in diagnosing, repairing, and modifying electrical systems, focusing on the charging, ignition, and starter systems. The activity used a problem-based training approach and was held over two days at the Mechanical Engineering Laboratory of Universitas Muhammadiyah Jember. Participants included vocational students, beginner technicians, and micro-business operators. Evaluation was conducted through pre-tests and post-tests, practical observations, and satisfaction questionnaires. Results showed an increase in average scores from 51 to 86 and a high level of participant satisfaction. This training effectively strengthened participants’ technical competencies and contributed to community empowerment through practical automotive skills